Euthanasia - A comparative study from legal perspective / Suria Fadhillah Md Pauzi and Nadia Omar - Md Pauzi, Suria Fadhillah; Omar, Nadia (2005)
Euthanasia has become a debating topic around the world especially after the recent tragic case of Terri Schiaovo. Whether to permit Euthanasia or not is among the most contentious legal questions. Euthanasia, by definition, means the practice of assisting severely ill people to die, either at their request or by taking the decision to withdraw life support .The motive of the person who commits an act of euthanasia is to benefit the one who is suffering from terminally ill disease. Stedman's Medical Dictionary has two citations: 1) "a quite, painless death"; and 2) "the intentional putting to death by artificial means of persons with incurable disease or illness to death. This topic is far from simple as it raises not only legal but also ethical issue. When faced with their loved one's pain and suffering, many believe that it is part of civilisation to let them die in most dignified way and as painless as possible. On the other hand, anti-euthanasia group believe that it is God that gives life and, therefore, only God should take it away. Euthanasia involves killing and all killing is morally wrong. The paper will examine the present state of the law in selected jurisdiction around the world. Particular attention will be focused on the differential treatment of the law in those countries. Special reference will also be made to a recent case of Terri Schindler Schiavo (1963-2005).